Dogs and Rabies Control in Nakhon Srithammarat Municipal Area - อินทองคำ นพราชย์; ปรีชาญวินิจ อิงอร (Disease Control Journal, 2009)
Rabies is a zoonotic viral disease and serious public health problem, transmitted to humans through a wound (mainly animal bites and scratches). The incubation period varies from 2 weeks to 6 years (average 2 -3 months) depending on the amount of virus and site of inoculation. Dogs is the cause of environmental problems as well as rabies in human. Nakhon Srithammarat Municipal authority has to take responsible on this matter. The objective of this study was to control the dogs in order to control rabies and get rid of annoyance. Licensing of dogs at the early age of 4 months, rabies vaccination, taking photographs or giving ear marked tattoo or microchip implanted were included in the program of which operated from July 2006 to December 2008 (30 months). There were 7,921 dogs licensed, vaccinated, of which 6,113 were owned dogs and 1,788 were stray dogs. It was believed that the control program, by licensing and vaccination should reach at least 80% of dog population in Municipal area, estimated of 10,000 dog population, among which 6,500 were owned dogs, and 3,500 were stray dogs. Sterilization should decrease about 9,000 dog population, more or less. However dog population seemed to be stable due to the excess breeding of owned dogs or some unwanted problems, the owner still moved them out to be strayed. So specific strategies for this problem should not be operated by the government alone, but creating public awareness and acceptance that rabies and environmental problems from dogs were everyone’s problem and responsibility should be accompanied.